Management of Posterior Segment Intraocular Foreign Body with Vitrectomy; Visual and Anatomical Outcome - Shah, Ritesh Kumar; Byanju, Raghunandan; Pradhan, Sangeeta (Journal of Universal College of Medical Sciences, 2018)
AIM: To evaluate the anatomical and visual outcome following removal of intraocular foreign body (IOFB) through pars planavitrectomy. MATERIAL & METHODS: A retrospective analysis of 11 cases of retained posterior segment foreign body that underwent pars planavitrectomy for removal of foreign body during the period of January 2013 to August 2017 was conducted. Demographics of patients, mechanism and details of injury, Snellen best corrected visual acuity, examination results at presentation and after surgery, any diagnostic imaging and surgical procedure were recorded and analysed. RESULTS: Out of eleven eyes of eleven patients (mean age= 25.4}8.6, range 22 50 years; all male) preoperative retinal detachment and endophthalmitis was seen in 27.3% and 36.4% of cases respectively. Eighty-two percent of cases presented within 17 days of sustaining injury. Foreign body size ranged from 2mm to 8 mm and all were magnetic metal. After vitrectomy and removal of foreign body, the number of eyes with vision of hand motion or worse decreased from 72.7% to 27.3%. Similarly 45.5% of eyes gained best corrected postoperative visual acuity of better than 6/60. Anatomical success could be achieved in 81.8% of eyes. CONCLUSION: Anatomical outcome following vitrectomy in eyes with retained posterior segment IOFB in terms of retinal attachment is sufficient; however, visual outcome can be affected by other collateral ocular injuries and their sequelae. Journal of Universal College of Medical Sciences, Vol. 5, No. 2, 2017, Page: 45-48